Guilt strikes at Granger's Store - Shames, Terry (Shames, Terry. Samuel Craddock mystery, 2023)
"Chief of Police Samuel Craddock is perplexed by a series of increasingly troubling events at Granger's Store. The shop owner's son, Mark Granger, has plans to renovate and modernise the popular animal feed store in the small Texas town of Jarret Creek. But when he's assaulted, its clear that some town folk are against his ideas. Could the devastating fire that follows be linked to the threatening phone calls Mark has been receiving? When the body of an outsider originally from Jarret Creek is found in the scorched shop, Craddock's investigation takes a sudden deadly turn. Who is determined to stop the renovation at any cost, and why? As Craddock investigates, he unearths dark secrets stretching back thirty years . . ."--